Feijoa (Acca sellowiana) wastes flour: chemical characterization, sensory acceptance and purchase intention of cookies (Research, Society and Development, 2021)
The aim of this study was to carry out the physical-chemical characterization of the feijoa residue flour (FRF) and to verify the potential of its use in cookies, through its technological properties and sensory acceptance. The FRF was obtained from drying at 55 °C and grinding the residues (endocarp and mesocarp) of the feijoa, being physically-chemically characterized (centesimal composition, pH, ATT, total carotenoids, ascorbic acid and mineral composition) and in the preparation cookies with partial replacement of wheat flour (F1-10% FRF and F2-20% FRF), with subsequent analysis of technological characteristics and sensory acceptance test. FRF stood out in relation to its total dietary fiber content (40.50 g/100g) and proved to be an important and potential source of essential elements. Cookies with FRF had the highest averages of global acceptance, and the F2 sample had the highest acceptability rate (88.17%). All the averages of the scores assigned by the tasters in the acceptability test, for samples F1 and F2, were close to 8 on the hedonic scale, demonstrating that the tasters “liked it a lot”. The purchase intention test reproduced the acceptability of the tasters, with the mean scores for the samples corresponding to “certainly buy” and “probably buy” on the hedonic scale of purchase intention. The results obtained in this study show the potential of using FRF, which can contribute to the diversification of the offer of products, in addition to adding value to the residue from the processing of a native fruit with potential nutritional characteristics.